PKM kelompok guru dengan upgrading materi Matematika Olimpiade di SDIT Ar-Rahmah Makassar - Muhammad Abdy; Syafruddin Side (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community Partnership Program (PKM) activity was carried out at SDIT Ar-Rahmah Makassar City. The purpose of this activity is to: a) increase the knowledge and skills of teacher groups in understanding elementary school Olympics mathematics concepts; b) increase the knowledge and skills of teacher groups in understanding the Olympics mathematical concepts; and c) enhance partner's knowledge and skills in learning elementary school Olympics math concepts. The problems of partners are: a) The lack of knowledge and skills of partners about elementary school Olympics mathematics learning; b) Low knowledge and skills of partners about understanding elementary school Olympics math concepts; and c) Lack of knowledge and skills of partners in understanding elementary school Olympics mathematics concepts. The method used is training, mentoring, and discussion between implementers and partners. This method is carried out to a group of 10 people and then evaluation and monitoring is carried out periodically for 3 months. Expected outcomes are: 1) Skills and insight changes in partner groups; 2) Ability and skills of partner groups in solving problems understanding elementary school olympiad mathematical concepts and 2) Publications in the mass media or the journal with ISSN number